2011
DOI: 10.1038/leu.2011.27
|View full text |Cite
|
Sign up to set email alerts
|

Association of polymorphisms in the TLR4 gene with the risk of developing neutropenia in children with leukemia

Abstract: Infections are a major cause of morbidity and mortality in children with acute lymphoblastic leukemia (ALL). Susceptibility to infections increases as the neutrophil count decreases. Despite identical treatment patients vary considerably in the number of neutropenic episodes. Toll-like receptor 4 (TLR4) has been shown to have a role in inhibiting apoptosis of neutrophils. Therefore, we hypothesized that polymorphisms in the TLR4 gene may influence the number of chemotherapyinduced neutropenic episodes. Eight s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
19
1

Year Published

2011
2011
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(21 citation statements)
references
References 32 publications
1
19
1
Order By: Relevance
“…A similar result was found in the previous study, which indicated that rs1927911 was not associated with DR in an Indian and a South Korean population 20 32. Contrary to our observation, rs1927911 was found to be associated with a lower risk of myocardial infarction in an American population, and the SNP was reported to have an increased risk of developing chemotherapy-induced neutropenia in a Caucasus population 33 34. With respect to the TLR4 variant rs10759931, no significant difference between the two groups was revealed concerning the allele and genotype of this SNP.…”
Section: Discussioncontrasting
confidence: 99%
“…A similar result was found in the previous study, which indicated that rs1927911 was not associated with DR in an Indian and a South Korean population 20 32. Contrary to our observation, rs1927911 was found to be associated with a lower risk of myocardial infarction in an American population, and the SNP was reported to have an increased risk of developing chemotherapy-induced neutropenia in a Caucasus population 33 34. With respect to the TLR4 variant rs10759931, no significant difference between the two groups was revealed concerning the allele and genotype of this SNP.…”
Section: Discussioncontrasting
confidence: 99%
“…Another study showed a combined effect of TLR4 3725G>C and miR-146a G>C gene polymorphisms for risk of gastric atrophy, but not for GC [43]. Our data on TLR4 3725G>C genotype frequencies are comparable to the reported frequencies in leukemia study on Caucasian population [44]. We did not find significant association between TLR4 3725G>C genotypes and HRAG or GC.…”
Section: Discussionsupporting
confidence: 75%
“…Various epidemiological studies also suggest that these SNPs in the innate immune system may influence the risk of patients to serious infection [36]. Budulac et al (2011) have shown the association of TLR4 polymorphisms with infection status and disease outcome in Chronic Obstructive Pulmonary Disease while Miedema et al (2011) showed that TLR4 polymorphisms were associated with risk of developing neutropenia in leukemic children [37, 38]. The remaining three SNPs were rs11536858, rs1927911, and rs1927914 of TLR4 gene and have been shown to be associated with several inflammatory diseases including cancer [10].…”
Section: Discussionmentioning
confidence: 99%